Interactive analysis of individual consumption patterns with regard to raw-material availability: The web tool My Raw Material World - Gerd Ahlert; Frank Hohmann; Michael Lettenmeier; Christa Liedke; Mark Meyer; Sören Steger (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2016)
On behalf of the German Federal Environment Agency (UBA) the research project ,,Global nachhaltige materielle Wohlstandsniveaus“ analysed material needs for German households' spending on durable consumer goods. Based on these findings, prototypical household endowments can be classified within the boundary conditions of global fairness and sustainable resource use. The applied classification scheme is based on the methodological concept of availability corridors which was developed and implemented over the project term by the Institute of Economic Structures Research (GWS) and the Wuppertal Institute for Climate, Environment and Energy. This methodological research has been accompanied by software development activities: A handy, easy understandable and instructive web tool ( http://resourcetool.gws-os.com/ ) has been established which illustrates the main findings of the research project in an intuitive way. Users can experience the research topic "raw material consumption and sustainability" in the context of own household endowments and identify the implied material needs of individual consumption patterns.
Keywords: A2; E6; Q3; 330; availability corridor; disposition corridor; sustainability; global fairness; durable home appliances; raw materials inventory; useful live; web tool